New CaV1.2 channelopathy with high-functioning autism, affective disorder, severe dental enamel defects, a short QT interval, and a novel cacna1c loss-of-function mutation - Endres, Dominique; Decher, Niels; Röhr, Isabell; Vowinkel, Kirsty; Domschke, Katharina; Komlosi, Katalin; Tzschach, Andreas; Gläser, Birgitta; Schiele, Miriam A.; Runge, Kimon; Süß, Patrick; Schuchardt, Florian; et al. (International Journal of Molecular Sciences, 2020)
Complex neuropsychiatric-cardiac syndromes can be genetically determined. For the first time, the authors present a syndromal form of short QT syndrome in a 34-year-old German male patient with extracardiac features with predominant psychiatric manifestation, namely a severe form of secondary high-functioning autism spectrum disorder (ASD), along with affective and psychotic exacerbations, and severe dental enamel defects (with rapid wearing off his teeth) due to a heterozygous loss-of-function mutation in the CACNA1C gene (NM_000719.6: c.2399A > C; p.Lys800Thr). This mutation was found only once in control databases; the mutated lysine is located in the Cav1.2 calcium channel, is highly conserved during evolution, and is predicted to affect protein function by most pathogenicity prediction algorithms. L-type Cav1.2 calcium channels are widely expressed in the brain and heart. In the case presented, electrophysiological studies revealed a prominent reduction in the current amplitude without changes in the gating behavior of the Cav1.2 channel, most likely due to a trafficking defect. Due to the demonstrated loss of function, the p.Lys800Thr variant was finally classified as pathogenic (ACMG class 4 variant) and is likely to cause a newly described Cav1.2 channelopathy.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Autism; CACNA1C; CaV1.2; Dental enamel defect; Short QT syndrome